Requirements to agricultural aviation - Буланов, В. В.; Дибир, А. Г. (Proceedings of National Aviation University (archive), 1999)
Substantiated is the necessity to renovate the stock of agricultural aviation. Presented are the requirements to agricultural aircrafts